1966
DOI: 10.1002/pssb.19660160234
|View full text |Cite
|
Sign up to set email alerts
|

On the Critical Resolved Shear Stress of Solid Solutions Containing Coherent Precipitates

Abstract: A quantitative estimate is made of the increase Δτ0 of the critical resolved shear stress for the case of solid solutions containing spherical and coherent precipitates. The interaction between edge dislocations and the coherency strain fields is believed to be the strengthening mechanism. The calculation is applied to experimental measurements on Al‐Zn and CuCo alloys. For small particles (R/b < 20) the dislocations tend to cut through the precipitates, whereas for larger particles the Orowan mechanism becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
2

Year Published

1972
1972
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(87 citation statements)
references
References 12 publications
1
83
1
2
Order By: Relevance
“…The larger Burger's vector of the superpartials, inevitably gives a greater elastic energy. Furthermore, the core energy of the dissociated configuration in Equation (19) would only be lower than that in (18) if the SISF energy is very low [6]. Taking this into account, Kear et al [21] proposed another configuration that could possess a lower core energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger Burger's vector of the superpartials, inevitably gives a greater elastic energy. Furthermore, the core energy of the dissociated configuration in Equation (19) would only be lower than that in (18) if the SISF energy is very low [6]. Taking this into account, Kear et al [21] proposed another configuration that could possess a lower core energy.…”
Section: Resultsmentioning
confidence: 99%
“…The simulations carried out used periodic boundary conditions and a system size of 660×180×32. One should bear in mind, however, that omitting lattice misfit from the model means that the effects of coherency hardening [18,19] are taken to be negligible. In comparison, most modern superalloys exhibit a significant negative lattice misfit, i.e.…”
Section: Model Formulation and Proceduresmentioning
confidence: 99%
“…Several studies have sought to quantify the effect of lattice misfit and coherency strengthening on the mechanical properties of superalloys [72,[75][76][77][78][79]. Gerold and Haberkorn [75] used rigorous mathematical analyses combining linear elasticity theory with statistical approximations to formulate the interactions of the precipitate stress field with a dislocation, assuming a spherical stress field, a straight dislocation line and an elastically isotropic matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Gerold and Haberkorn [75] used rigorous mathematical analyses combining linear elasticity theory with statistical approximations to formulate the interactions of the precipitate stress field with a dislocation, assuming a spherical stress field, a straight dislocation line and an elastically isotropic matrix. The results obtained in their study, indicated that for an edge dislocation, the change in the CRSS should be proportional to the absolute value of δ 3/2 .…”
Section: Discussionmentioning
confidence: 99%
“…Now, in order to obtain the value for the increment in proof stress, the contribution from the coherency strain-field should be taken into aocount. The calculation on the basis of the theory by Gerald (10) shows that for the case of Udimet 520 this contribution amounts to 5 kg/&m? By the addition of the calculated value for the effect of the coherency strain field to eq.…”
Section: O-5mentioning
confidence: 99%